Relative age effect is widespread among most successful youth, but not in senior Olympic weightlifters - Bezuglov, E.; Morgans, R.; Kapralova, E.; Achkasov, E.; Telyshev, D.; Sadkovaya, O.; Malyakin, G. I. (Journal of Human Kinetics, 2025)
The aim of the study was to investigate the prevalence of the relative age effect (RAE) among elite Olympic weightlifters in different age groups. The prevalence of RAE was studied among top 10 participants from the World Weightlifting championships for youth, junior and senior age groups and from the Olympic Games from 2009 to 2022. Birth dates of 3886 athletes were analyzed and further divided into four groups according to the birth quartile. Weight categories were grouped as lightweight, middleweight and heavyweight. The effect was found among lightweight and heavyweight girls, boys of all weight groups, lightweight and middleweight junior females and juniors of all weight groups. In the senior group, RAE was only present among heavyweight males. Differences in the prevalence of RAE between male and female weightlifters were statistically significant (p = 0.009). Differences in effect between youth and junior age groups were not significant (p = 0.24). The findings of this study demonstrate that RAE tends to be widespread among the best weightlifters of both sexes in youth and junior age groups, but disappears in most weight groups at the elite senior level.